Cross-subject comparison of local diffusion MRI parameters - Smith, S; Kindlmann, G (Elsevier, 2009)
The diffusion of water in brain tissue is affected by the local tissue microstructure. Magnetic resonance diffusion imaging is sensitive to these effects, and, in addition to tractography-based studies of long-range connectivity information, there has been a great deal of interest in using voxelwise measures derived from diffusion data as local markers of the tissue microstructure. Diffusion anisotropy describes how variable the diffusion is in different directions and is most commonly quantified via a measure known as fractional anisotropy. Registration is the spatial adjustment of one image to match another. The contents of the "input" image are moved around within the image matrix until they are well aligned with the contents of the "reference" image. Localized/voxelwise analysis of multi-subject diffusion MRI data has a clear role to play, for example in tracking changes in white matter caused by disease. Although careful tractography-based analyses will increasingly have a role to play, whole-brain voxelwise analyzes provide a powerful complement to such approaches, by allowing the entire data set to be investigated in a straightforward manner. The strengths of VBM-style voxelwise analyses are that they are fully automated, simple to apply, investigate the whole brain, and do not require pre-specifying and pre-localizing regions or features of interest. The main limitation relates to problems caused by alignment inaccuracies, including the danger of misinterpreting apparent results in voxels that do not in fact correspond to white matter in all subjects. © 2009 Copyright © 2009 Elsevier Inc. All rights reserved.